Personal value system as related to anti-minority attitude in Muslim students of Rajshahi University, Bangladesh - Muhammad, Noor; Latif, Md Abdul (Journal of Life and Earth Science, 2011)
Relationships between personal values and anti-minority attitude in a group of 100 Muslim students of Rajshahi University were estimated using adapted Bengali versions of Allport-Vernon-Lindzey study of values and Levinson-Sanford Anti-Semitism scale. The relationships between anti-minority attitude and each of the Spranger’s six values were computed to calculate the co-efficient of correlation between the scores on each of the six value scales and the scores on anti-minority attitude scale. Results show that a significant positive correlation exists between political and economical values and anti-minority attitude (P<0.01) while a significant negative correlation exists between theoretical, aesthetic, social and religious values and anti-minority attitude (P<0.01). For further analyzing the relationships that exists between Spranger’s six values and antiminority attitude, the distribution of the latter was divided into four quarters and statistical comparisons were made among them on the basis of the scores of each value scale employing t-test. Statistical significant differences in values were found between the low (1st quarter) and high (4th quarter) anti-minority attitude groups, indicating that high anti-minority attitude is dominated by political and economic values, while low anti-minority attitude is dominated by religious, theoretical, aesthetic and social values. Key words: Personal value system; anti-minority attitude; prejudice; majority and minority groups; Muslim students; Rajshahi University DOI: 10.3329/jles.v5i0.7356 J. Life Earth Sci., Vol. 5: 85-89, 2010